Translating Transcultural Literature: Cultural Translation Squared - Elena V. Beloglazova (Vestnik Volgogradskogo Gosudarstvennogo Universiteta. Seriâ 2. Âzykoznanie, 2023)
The present paper focuses on external language-based culture presentation, which can result from two distinct kinds of translation – the traditional translation, departing from a culturally loaded text, and the translation of culture, departing directly from the culture being presented. Despite the fact that in both instances we deal with translation and similar linguistic mechanisms are being involved, the comparative study of a transcultural text of L. Tolstoy’s Hadji Murad and its translation into English allows to demonstrate significant distinctions between the two modes of translation. At that, the distinctions affect such core features of translation as its accuracy and readability. In particular, the study revealed that the direct translation of culture, being unconditioned by the source text and the derivative status, tends to be more precise in rendering the specific features of a unique culture it deals with, introducing xenonymic elements at the expense of language homogeneity. While in traditional text-to-text translation, striving to comply with the requirements of readability and normality, cultural meanings appear to be much more prone to neutralizing and distorting. The presented study demonstrates that the losses and distortions we associate with translation are not inevitable and can be minimized. The practice underlying the translation of culture can serve as a source of a strategy fit to deal with culturally loaded texts.